Vision enhancement and language learning: A critical analysis of vision-building in an English for Academic Purposes programme - Vlaeva, Denny; Dörnyei, Zoltán (Language teaching research : LTR, 2021)
Future second language (L2) self-images have proven integral to L2 motivation, prompting several attempts to purposefully develop learners’ ideal L2 selves over the past decade through the use of vision-building techniques. Some of these ‘vision interventions’ have reported successfully enhancing learners’ L2 self-images and motivation; other studies, however, diverge from an unqualified success narrative, citing for example a lack of increase in learner effort despite stronger future vision. Data collection has also been typically restricted to the period of the intervention itself, and so insight into the long-term take-up of the introduced techniques, or how potential outcomes develop over time, remains limited. To gain further understanding into such issues, we have charted the evolving nature of the L2 vision intervention over the past decade, and complemented the learning from previous studies by conducting a five-week vision-building course with 25 learners of English for academic purposes (EAP) in the UK university-pathway system. Interview data gathered over the course of 10 months – the longest investigation of vision-building we are aware of – demonstrated fluctuating engagement with visualization, and accordingly, our analysis looks critically at the notion of self-image-centred intervention in instructed second language acquisition (SLA). While we believe that L2 vision can indeed be consciously enhanced, we argue that success depends largely on how general principles are adapted to specific learning contexts. The discussion highlights challenges that instructors may encounter in staging such interventions, and offers practical lessons for using self-images in the classroom.